Multidetector Computed Tomographic Characterization of a Rare Retroperitoneal Mass in the Left Psoas Compartment - Rochita Venkata Ramanan; Elankumaran Krishnan; Maya Menon; Ponneyinchelvi Shivanandan (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
We discuss a case of a rare, large, left-sided retroperitoneal mass that presented a diagnostic difficulty in characterization both radiologically and pathologically. We analyze the imaging findings in a step-by-step manner to understand its structure of origin, components, and tissue characterization. Intraoperative images are correlated with multidetector computed tomographic (CT) scan images to demonstrate spatial orientation. A discussion of the pathological findings, and conclusions are made. This discussion highlights the methodology by which radiologic diagnosis is made on multidetector CT scans.